2017
DOI: 10.1155/2017/9679470
|View full text |Cite
|
Sign up to set email alerts
|

Use of Common Inflammatory Markers in the Long-Term Screening of Total Hip Arthroprosthesis Infections: Our Experience

Abstract: Orthopedic implants have become essential components of modern medicine. The risk of infection of total hip arthroplasty (THA) is 1.5%−2%. Are the C-reactive protein (CRP), the erythrocyte sedimentation rate (ESR), and procalcitonin (PCT) good markers for THA infection screenings? From February 2009 to December 2012 at our Department of Orthopedics and Traumatology, 1248 patients were treated with THA. No prosthesis was cemented. All patients received antibiotic prophylaxis. All patients were discharged approx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
0
23
0
1
Order By: Relevance
“…These markers are valuable support for the surgeon in monitoring early postoperative superficial pin-tract infection of the circular external fixator in periprosthetic fractures around the knee. We conducted postoperative evaluation for the prevention of pin-tract infection, using ESR and CRP levels as common inflammatory markers [33].…”
Section: Discussionmentioning
confidence: 99%
“…These markers are valuable support for the surgeon in monitoring early postoperative superficial pin-tract infection of the circular external fixator in periprosthetic fractures around the knee. We conducted postoperative evaluation for the prevention of pin-tract infection, using ESR and CRP levels as common inflammatory markers [33].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, correlation between NRBC count and laboratory indexes showed that NRBC was positively correlated with CRP, PCT and RDW, negatively correlated with RBC, Hb and Hct, but not significantly correlated with SAA, WBC and PLT. CRP, PCT and RDW were commonly used inflammatory indexes [43], RBC, Hb and Hct were visual indexes to reflect whether anemia exists in the body [44], PLT could reflect the coagulation or thrombus state of patients [45], so it can be inferred that the production and release of NRBC in ICU patients were related to inflammation and anemia, but not to whether the body was in hypercoagulable state. Moreover, NRBC was positively correlated with APACHE Ⅱ score, SOFA score and CCI, and the above three clinical scores are generally recognized as indicators for disease severity assessment and prognosis [46].…”
Section: Disscussionmentioning
confidence: 99%
“…When sampling tissue, 3 to 4 tissue samples should be obtained when treating PJI to facilitate organism identification and antimicrobial management, in the experience of 2 institutions 42,43 . Markers for PJI that were studied include presepsin 44 , adenosine deaminase 45 , procalcitonin 46,47 , interleukin-6 (IL-6) 48 , leukocyte esterase [49][50][51][52] , alpha-defensin [53][54][55] , D-dimer 56 , receptor activator of nuclear factor-kB ligand (RANKL), and osteoprotegerin 57 . Centrifugation of synovial fluid samples at 2,000 · gravity for 15 minutes improves leukocyte esterase testing, but testing should be performed on the top 2 mm of the centrifuged sample 58 .…”
Section: Diagnosismentioning
confidence: 99%